American Indians - Starr, Frederick, 1858-1933 (Salt Lake City, UT : Project Gutenberg, 2011)
"American Indians" by Frederick Starr is a historical account written in the late 19th century. This work aims to educate young readers about the diverse cultures, lifestyles, and histories of Native American tribes, emphasizing the rapidly changing nature of their societies. The book is structured into various chapters covering different aspects of Indian life, including housing, dress, and customs, aiming to provide a comprehensive picture of their existence. At the start of the book, the author outlines the purpose of the work, noting its intention as a reading resource for children, and emphasizes the importance of understanding the lives of American Indians who are "rapidly dying off or changing." The preface introduces significant topics that will be discussed, such as the classification of tribes, their languages, and the survival challenges they faced historically. The opening portion delves into the general facts about American Indians, including their physical descriptions, cultural diversity, and their communal lifestyles, contrasting the common misconception of them being solely nomadic hunters. This foundation sets the stage for a deeper exploration of the various tribes, their traditions, and their interactions with the wider world. (This is an automatically generated summary.)
Release date is 2011-04-18
Keywords: Indians of North America